Nurses’ Communication to Patients and Associated Factors at East Gojjam Zone, Governmental Hospitals, Amhara Region, Ethiopia, 2022: An Institution-Based Cross-Sectional Study - Kindie L; Mitiku HZ; Muche M; Wondimneh BY; Geletie HA (Dove Medical Press, 2024)
Liyew Kindie,1 Haymanot Zeleke Mitiku,1 Mikyas Muche,1 Bayu Yimenu Wondimneh,1 Haymanot Abebe Geletie2 1Department of Nursing, Debre Markos University, Debre Markos, Ethiopia; 2Department of Nursing, Wolkite University, Wolkite, EthiopiaCorrespondence: Liyew Kindie, Department of Nursing, Debre Markos University, P.O.box: 269, Debre Markos, Ethiopia, Tel +251918527368, Fax +251587780673, Email liyewkindie21@gmail.comPurpose: This study aims to assess nurses' communication with the patient and associated factors at East Gojjam Zone governmental hospitals, Amhara Region, Ethiopia, 2022.Methods: An institution-based cross-sectional study design was conducted among 378 study participants, from April 20/2022 to May 30/2022 at East Gojjam Zone governmental hospitals, Amhara Region, Ethiopia, 2022. A simple random sampling technique was utilized to select nurses from each hospital. Nurses' communication with the patient was measured by observation and a standardized checklist. The data were entered into Epidata version 4.6 and then exported to the Statistical software package for social science (SPSS) version 25 for analysis. A binary logistic regression model was used to identify factors associated with the nurse's communication with the patient. Variables with p-value ≤ 0.25 in the bivariable analysis were entered into the multivariable analysis. Thus, the association was considered statistically significant with a p-value < 0.05 at a 95% confidence interval.Results: A total of 378 nurses participated in the study, with a response rate of 96.4%. Out of this 215 (56.9%), with 95% CI (51.86- 61.89%), had ineffective communication with the patient. In multivariable analysis, variables such as lower education level [AOR: 1.90, 95% CI (1.175- 3.096)], shorter work experience [AOR: 2.163, 95% CI (1.143- 4.091)], not taken communication skill training [AOR: 2.154, 95% CI (1.341- 3.458)] and higher work overload [AOR: 2.084, 95% CI (1.255- 3.460)] were factors significantly associated with ineffective communication.Conclusion and Recommendation: In this study, nearly 57% of nurses' had ineffective communication with the patient. Lower education level, shorter work experience, not taken communication skill training, and higher work overload are significantly associated with ineffective communication. Hospital authorities and other health-sector stakeholders should consider providing continuous communication skill training, adequate educational opportunities for nurses, and recruiting an adequate number of nurses.Keywords: communication, nurse, patient, hospital